Enhanced Second‐Harmonic Generation in a Single Microwire Based on Localized Surface Plasmon. Issue 10 (29th May 2019) - Li, Jinyu; Zhu, Hai; Chen, Zhiyang; Huang, Ying; Zheng, Huying; Tang, Ziying; Gui, Xuchun; Wang, Shuangpeng; Tang, Zikang; Ni, Peinan; Genevet, Patrice
Abstract : The properties of enhanced second‐harmonic generation (SHG) in microwires (MWs) through surface plasmonics have been investigated comprehensively. Here, the high Q‐factor hexagonal microcavity of a single MW can significantly confine the fundamental frequency of light. Moreover, randomly distributed Ag nanoparticles are fabricated on a template plate, which is used to enhance the SHG through localized surface plasmon (LSP). Compared with a bare MW, the intensity of the SHG based on LSP can be enhanced twofold at room temperature. It is seen that the LSP effect on SHG is sensitive to temperature, and the enhancement ratio partly increases linearly with decreasing temperature, which can be explained by the dependence of the metal dielectric permittivity on the temperature according to the Drude model. Abstract : The second‐harmonic generation (SHG) based on single ZnO microwire is produced via micro‐optical system. Notably, the intensity of the SHG signal can be modulated by the whispering gallery mode and enhanced twofold by Ag nanoparticles at room temperature. The dependence of localized surface plasmon (LSP) effect through Ag nanoparticles on the temperature is investigated in detail in the paper.